GCH1 mutations in hereditary spastic paraplegia. Issue 1 (18th March 2021) - Varghaei, Parizad; Yoon, Grace; Estiar, Mehrdad A.; Veyron, Simon; Leveille, Etienne; Dupré, Nicolas; Trempe, Jean‐François; Rouleau, Guy A.; Gan‐Or, Ziv
Abstract: GCH1 mutations have been associated with dopa‐responsive dystonia (DRD), Parkinson's disease (PD) and tetrahydrobiopterin (BH4 )‐deficient hyperphenylalaninemia B. Recently, GCH1 mutations have been reported in five patients with hereditary spastic paraplegia (HSP). Here, we analyzed a total of 400 HSP patients (291 families) from different centers across Canada by whole exome sequencing (WES). Three patients with heterozygous GCH1 variants were identified: monozygotic twins with a p.(Ser77_Leu82del) variant, and a patient with a p.(Val205Glu) variant. The former variant is predicted to be likely pathogenic and the latter is pathogenic. The three patients presented with childhood‐onset lower limb spasticity, hyperreflexia and abnormal plantar responses. One of the patients had diurnal fluctuations, and none had parkinsonism or dystonia. Phenotypic differences between the monozygotic twins were observed, who responded well to levodopa treatment. Pathway enrichment analysis suggested that GCH1 shares processes and pathways with other HSP‐associated genes, and structural analysis of the variants indicated a disruptive effect. In conclusion, GCH1 mutations may cause HSP; therefore, we suggest a levodopa trial in HSP patients and including GCH1 in the screening panels of HSP genes. Clinical differences between monozygotic twins suggest that environmental factors, epigenetics, and stochasticity could play a role in the clinical presentation. Abstract :